Investigation of electrochemical corrosion behavior of additive manufactured Ti–6Al–4V alloy for medical implants in different electrolytes - Sharma, Ashutosh; Oh, Min Chul; Kim, Jung Taek; Srivastava, Ashok K.; Ahn, Byungmin (Journal of Alloys and Compounds, 2020)
There is increasing concern about the surface degradation of bioimplants in various corrosive environments. The dissolution of implant materials may cause an inflammatory reaction with internal organs and can be fatal. Here, the corrosion properties of selective laser melted Ti–6Al–4V (SLM Ti–6Al–4V) were investigated in different corrosive media (NaOH, NaCl, H2SO4 and simulated body fluid (SBF)). The corrosion tests were conducted by potentiodynamic polarization and electrochemical impedance spectroscopy coupled with optical and scanning electron microscopy. A commercial cast Ti–6Al–4V alloy sample was used as a reference for comparison. The results show that the polarization and charge transfer resistance of SLM and cast Ti–6Al–4V are considerably high in NaOH, SBF and NaCl, whereas extremely poor corrosion resistance occurs in a more aggressive solution (H2SO4). These results can be correlated to the abundant metastable αʹ-martensite phase and the higher surface porosity of the SLM Ti–6Al–4V alloy in comparision to the cast Ti–6Al–4V, which degrades the passivity. The corrosion resistance of all samples in the various media followed the order of (NaOH)cast Ti–6Al–4V > (NaOH)SLM Ti–6Al–4V > (SBF)cast Ti–6Al–4V > (SBF)SLM Ti–6Al–4V > (NaCl)cast Ti–6Al–4V > (NaCl)SLM Ti–6Al–4V > (H2SO4)cast Ti–6Al–4V > (H2SO4)SLM Ti–6Al–4V.
Keywords: Bio implants; Charge transfer resistance; Corrosive environment; Electrochemical corrosion behavior; Inflammatory reaction; Passivity; Simulated body fluids; Surface degradation; Additive manufacturing; Bioimplant; Corrosion; Passivity; Selective laser melting